2017
DOI: 10.1016/j.annals.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The female tourist experience in Egypt as an Islamic destination

Abstract: In Islamic destinations female tourists face the added challenge of negotiating their way through male constructed local norms. This paper fills the gap in gender and tourism research with a focus on female tourists' experiences in Egypt as an Islamic destination, outlining the diverse ways in which gender shapes and influences their experiences. A qualitative approach was taken to explore women's coping strategies with the male sexualised gaze that they encountered during their holiday in Egypt, and sheds lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 38 publications
1
77
0
6
Order By: Relevance
“…As indicated in the methodology section, the number of Muslim female respondents participated in the study were limited as most potential female respondents refused to take part in the study due to their busy schedules and social norms, which prevented them to take part in interviews without permission from their husbands. In their study, Brown and Osman () found that there is a significant difference in the female tourists' experiences, and therefore, it can be argued that the perceived values of female tourists may differ compared with male tourists. Therefore, conducting a similar study with more female Muslim participants using in‐depth interviews or focus groups would also be beneficial, to provide insights into the perceived values associated with halal holidays from a women's perspective.…”
Section: Resultsmentioning
confidence: 96%
“…As indicated in the methodology section, the number of Muslim female respondents participated in the study were limited as most potential female respondents refused to take part in the study due to their busy schedules and social norms, which prevented them to take part in interviews without permission from their husbands. In their study, Brown and Osman () found that there is a significant difference in the female tourists' experiences, and therefore, it can be argued that the perceived values of female tourists may differ compared with male tourists. Therefore, conducting a similar study with more female Muslim participants using in‐depth interviews or focus groups would also be beneficial, to provide insights into the perceived values associated with halal holidays from a women's perspective.…”
Section: Resultsmentioning
confidence: 96%
“…On the specific subject of aggressive harassment, emerging studies identify sexual harassment as a common but least‐reported tourist experience (Brown & Osman, ; Calafat et al, ). Seow and Brown () have likewise argued that sexualized male gaze is a major constraint for solo female travelers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regard gender‐based harassment, other authors contend that female tourists are usually the victims of sexual abuses with the commonest places being nightclubs and beaches (Brown & Osman, ; Calafat et al, ; de Albuquerque & McElroy, ). Pennington‐Gray and Kerstetter () also argued that female tourists have different expectations and attitudes to travel.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations